THE IMPLEMENTATION OF REFLECTIVE LEARNING MODEL PLUS TO IMPROVE PROPOSAL TEXT WRITING SKILLS OF XI SOCIAL 1 STUDENTS OF STATE SENIOR HIGH SCHOOL 4 JEMBER - Sofiatul Annisa; Nurhadi Nurhadi; Martutik Martutik (Erudio Journal of Educational Innovation, 2023)
This class action research aims to improve the ability to write proposal text of XI Social 1 students at State Senior High School 4 Jember by using reflective learning model plus. Based on the results of observations and interviews in class XI Social 1 of State Senior High School 4 Jember, it was found that only 13 students (37%) out of 35 students scored above the Minimum Mastery Criteria in learning to write proposal text. To overcome these problems, learning improvement was carried out by applying the reflective learning plus model. This study used a qualitative approach and a type of classroom action research consisting of two cycles. Each cycle consists of four stages, namely: (1) planning, (2) action implementation, (3) observation, and (4) reflection. The methods used to obtain data were observation, tests, interviews, and documentation. The results showed that students' ability to write proposal text increased from cycle I to cycle II. The number of students who reached the Minimum Mastery Criteria in cycle I was 27 students (77%) out of 35 students, while in cycle II 35 students (100%). Based on the results obtained, it can be concluded that the application of reflective learning model plus can improve students' ability in writing proposal text.